Clinical utility of breath testing in irritable bowel syndrome - Sophie Brigstocke; Darren M. Brenner (Permanyer, 2024)
Breath tests (BT) have existed as a diagnostic tool since 1970s, but it is only recently that they are being used routinely by gastroenterologists to diagnose intestinal overgrowth (IO). Existing literature has validated that a subset of patients with irritable bowel syndrome (IBS) meet criteria for IO. However, the clinical utility of hydrogen and methane BT in the diagnosis and management of IBS remains a subject of ongoing debate, and existing guidelines do not consistently provide direction on how these tests should be used. This review explores what is currently known about IO as a potential driver of symptoms in patients with IBS and details the pearls and pitfalls of using BT to diagnose and treat both small intestinal bacterial overgrowth and intestinal methanogen overgrowth in patients with IBS.